Reshaping globalization : multilateral dialogues and new policy initiatives - edited by Andrea Krizsán and Violetta Zentai. (Central European University Press, 2003)
Papers from a conference organized by the Central European University in Budapest in October 2001.Includes bibliographical references and index.